Hubungan Tingkat Kecemasan Ibu yang Mempunyai Balita 12-14 Bulan dengan Pelaksanaan Imunisasi Dasar Lengkap Pada Masa Pendemi Covid 19 di Wilayah Kerja Puskesmas Koto Baru - Mimi Rosiska (Universitas Malahayati Lampung, 2022)
THE RELATIONSHIP OF ANXIETY LEVELS OF MOTHERS WHO HAVE TODDLERS 12-14 MONTHS WITH COMPLETE BASIC IMMUNIZATION DURING THE COVID 19 PANDEMIC IN THE WORK AREA OF KOTO BARU HEALTH CENTER 2021. Public health center services, Posyandu especially immunizations do not run smoothly during this pandemic is due to anxiety, fear of bringing babies to puskesmas activities, posyandu.. The purpose of this study was to determine the relationship between the level of anxiety of mothers who have toddlers 12-14 months with the implementation of complete basic immunization during the COVID-19 pandemic in the Tanjung Puskesmas Working Area, Koto Baru Health Center in 2021. The type of research used is analytic with a cross-sectional approach which will be conducted in August 2021. These are subjects who meet the established criteria. The population in this study were all mothers who had toddlers aged 12-14 months with a total population of 154 people in the Koto Baru Health Center in 2021 using the Simple Random Sampling technique. Data was collected using a questionnaire, then the data was processed and analyzed by descriptive and bivariate univariate with chi-square and correlation tests. The results showed that more than half (59.4%) of respondents with moderate levels of maternal anxiety, more than half (53.1%) of respondents who did not complete basic immunization for infants aged 12-14 months, with a (p-value of 0.014). It means that there is a relationship between the level of anxiety of mothers who have toddlers 12-14 months with the implementation of complete basic immunization during the COVID-19 pandemic in the Koto Baru Health Center in 2021. It is hoped that the puskesmas can provide health information about the benefits of the relationship between the anxiety levels of mothers who have toddlers 12-14 months with the implementation of complete basic immunization during the COVID-19 pandemic. Keywords: Maternal Anxiety Level, Implementation of Complete Basic Immunization during the Covid 19 Pandemic. INTISARI: HUBUNGAN TINGKAT KECEMASAN IBU YANG MEMPUNYAI BALITA 12-14 BULAN DENGAN PELAKSANAAN IMUNISASI DASAR LENGKAP PADA MASA PANDEMI COVID 19 DI WILAYAH KERJA PUSKESMAS KOTO BARU TAHUN 2021. Pelayanan Puskesmas, Posyandu khususnya pemberian imunisasi tidak berjalan dengan lancar pada masa pendemi ini hal ini disebabkan adanya rasa kecemasan, ketakutan membawa bayi kekegiatan puskesmas, posyandu.Tujuan penelitian ini untuk mengetahui hubungan tingkat kecemasan ibu yang mempunyai balita 12-14 bulan dengan pelaksanaan imunisasi dasar lengkap pada masa pandemi covid 19 di Wilayah Kerja Puskesmas Koto Baru Rawang Tahun 2021.Jenis penelitian yang digunakan adalah analitik dengan pendekatan cross sectional yang dilaksanakan bulan Agustus 2021.ini adalah subjek yang memenuhi kriteria yang telah ditetapkan. Populasi pada penelitian ini adalah seluruh ibu-ibu yang mempunyai balita usia 12-14 bulan dengan jumlah populasi 154 orang di Wilayah Kerja Puskesmas Koto Baru Rawang Tahun 2021dengan teknik Simple Random Sampling. Pengumpulan data dilakukan dengan kuesioner, kemudian data diolah dan dianalisis secara univariat deskriptif dan bivariat dengan uji chi-square dan korelasi.Hasil penelitian diperoleh lebih dari separuh (59,4%) responden dengan tingkat kecemasan sedang ibu, lebih dari separuh (53,1%) responden tidak lengkap pelaksanaan imunisasi dasar lengkap bayi usia 12-14 bulan, dengan (p value 0,014). Berarti terdapat hubungan tingkat kecemasan ibu yang mempunyai balita 12-14 bulan dengan pelaksanaan imunisasi dasar lengkap pada masa pandemi covid 19 di Wilayah Kerja Puskesmas Koto Baru Tahun 2021. Disarankan kepada ibu yang mempunyai balita 12-14 bulan agar dapat meningkatkan pelaksanaan imunisasi dasar lengkap pada masa pandemic covid 19 ini, supaya dapt meningkatkan kekebalan dari penyakit. Kata kunci:Tingkat Kecemasan Ibu, Pelaksanaan Imunisasi Dasar Lengkap pada masa Pandemi Covid 19.